The Adenomatous polyposis coli tumour suppressor is essential for Axin complex assembly and function and opposes Axin's interaction with Dishevelled. - Mendoza-Topaz, C.; Mieszczanek, J.; Bienz, M. (Open biology, 2011)
Most cases of colorectal cancer are linked to mutational inactivation of the Adenomatous polyposis coli (APC) tumour suppressor. APC downregulates Wnt signalling by enabling Axin to promote the degradation of the Wnt signalling effector ?-catenin (Armadillo in flies). This depends on Axin's DIX domain whose polymerization allows it to form dynamic protein assemblies ('degradasomes'). Axin is inactivated upon Wnt signalling, by heteropolymerization with the DIX domain of Dishevelled, which recruits it into membrane-associated 'signalosomes'. How APC promotes Axin's function is unclear, especially as it has been reported that APC's function can be bypassed by overexpression of Axin. Examining apc null mutant Drosophila tissues, we discovered that APC is required for Axin degradasome assembly, itself essential for Armadillo downregulation. Degradasome assembly is also attenuated in APC mutant cancer cells. Notably, Axin becomes prone to Dishevelled-dependent plasma membrane recruitment in the absence of APC, indicating a crucial role of APC in opposing the interaction of Axin with Dishevelled. Indeed, co-expression experiments reveal that APC displaces Dishevelled from Axin assemblies, promoting degradasome over signalosome formation in the absence of Wnts. APC thus empowers Axin to function in two ways-by enabling its DIX-dependent self-assembly, and by opposing its DIX-dependent copolymerization with Dishevelled and consequent inactivation.